A review on IT outsourcing practices for e-business transformation among SMEs in Malaysia - Sabri S.M.; Sulaiman R.; Ahmad A.; Tang A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Economics; Electronic commerce; Outsourcing; Case study approach; E-business transformation; eBusiness; In-depth understanding; IT outsourcing; Literature reviews; SMEs; Virtual marketplace; Competition